The Analysis Study of Prevalence, Diagnosis and Management of Gestational Diabetes: A Comprehensive Years Systematic Review - Bayu Setyo Nugroho (The International Journal of Medical Science and Health Research, 2025)
Background: Gestational diabetes mellitus (GDM), a common endocrine disorder during pregnancy, is associated with the placental secretion of diabetogenic hormones, increasing insulin resistance. The worldwide prevalence of GDM is believed to be between 7% and 10% of all pregnancies, with diagnostic heterogeneity affecting prevalence and outcome estimates. The absence of globally recognized gold standards for GDM diagnosis leads to variability in identifying affected women. Methods: This systematic review complied with PRISMA 2020 requirements, concentrating solely on full-text papers published in English from 2014 to 2024. Editorials and review articles lacking a DOI were eliminated to guarantee the use of high-quality sources. A literature review was performed using esteemed databases such as ScienceDirect, PubMed, and SagePub to discover pertinent studies. Result: The initial database search identified more than 300 relevant publications on the topic. Following a comprehensive three-stage screening process, eight studies were selected that met the specified inclusion criteria for in-depth analysis. The studies were subjected to a thorough critical evaluation, enabling an in-depth analysis of the prevalence, diagnosis, and management of gestational diabetes. This targeted methodology ensured that the analysis employed strong evidence closely aligned with the study's objectives. Conclusion: GDM is a common medical complication in pregnancy that has a significant effect on both maternal and neonatal health outcomes globally. The prevalence ranges from 2% to 24.5%, demonstrating a continuous correlation between maternal glucose levels and adverse outcomes. Lifestyle interventions, dietary modifications, and regular physical activity are essential for the management of GDM.